Overseas GP recruitment: comparing international GP training with the UK and ensuring that registration standards and patient safety are maintained. Issue 2 (2019) - Fletcher, Emily; Sansom, Anna; Pitchforth, Emma; Curnow, Gerens; Freeman, Adrian; Hawthorne, Kamila; Campbell, John
No abstract available